The Effectiveness of Group Guidance Services in Improving the Emotional Intelligence of Malaysian Students - Ria Lezita Mardiana; M Fauzi Hasibuan (Universitas Negeri Medan, 2026)
Emotional intelligence is one of the key factors supporting the social and academic development of elementary school students; however, in reality, there are still students who struggle to manage their emotions, build positive social relationships, and express their feelings appropriately. This study aims to test the effectiveness of group counseling services in improving the emotional intelligence of elementary school students. This study uses a quantitative approach with a pre-experimental design through a One-Group Pretest–Posttest Design. The research subjects consisted of seven fifth-grade students from the Muhammadiyah Kepong Counseling Center in Malaysia who were categorized as having low emotional intelligence. Data collection was conducted using an emotional intelligence scale with five aspects: self-awareness, self-control, self-motivation, empathy, and social skills. The data were analyzed using statistical tests to determine differences in students’ emotional intelligence levels before and after receiving group counseling services. The results showed an increase in students’ emotional intelligence scores after participating in group counseling. This improvement was evident in students’ abilities regarding self-awareness and self-control, increased empathy, and the development of more positive social relationships with peers. Based on these findings, it can be concluded that group counseling services are effective in enhancing students’ emotional intelligence. Therefore, group counseling services can serve as one of the intervention strategies that guidance and counseling teachers or school counselors can implement to support students’ emotional and social development.